Magnetic–Thermal Coupling-Based Study on the Temperature Characteristics of Flameproof Cable Boxes for Coal Mines at Various Failure Modes - Hongkui Zhang; Zhaoxuan Cui; Yipeng Lan (Applied Sciences)
Temperature monitoring is the main indicator to ensure the safe operation of the coal mine explosion-proof box. In this study, a three-way flameproof cable box was considered for coal mines. A three-dimensional transient temperature field simulation model was constructed for magnetic–thermal coupling and subsequently used to conduct temperature field simulation for the failure of the flameproof cable box for coal mines. An experimental platform was developed to test the temperature characteristics of failure flameproof cable boxes for coal mines and obtain temperature curves at various failure currents. Using the experimental results of temperature characteristics and temperature field simulation outcomes, we analyzed the time responses and spatial distribution characteristics of the temperature rise of flameproof cable boxes for coal mines. The error between simulation and experimental results does not exceed 1 K, and the upper limit of time to ensure safe operation under different failure modes is determined. Thus, the acquired temperature distribution characteristics in a failure mode can be used as a reference for the design, inspection, and status warning of flameproof cable boxes for coal mines.